Isolation of Extracellular Vesicles From the Bronchoalveolar Lavage Fluid of Healthy and Asthmatic Horses - Höglund, Nina; Koho, Ninna; Rossi, Heini; Karttunen, Jenni; Mustonen, Anne-Mari; Nieminen, Petteri; Rilla, Kirsi; Oikari, Sanna; Mykkänen, Anna (Frontiers in Veterinary Science, 2022)
Extracellular vesicles (EVs) are membrane-bound particles that engage in inflammatory reactions by mediating cell–cell interactions. Previously, EVs have been isolated from the bronchoalveolar lavage fluid (BALF) of humans and rodents. The aim of this study was to investigate the number and size distribution of EVs in the BALF of asthmatic horses (EA, n = 35) and healthy horses (n = 19). Saline was injected during bronchoscopy to the right lung followed by manual aspiration. The retrieved BALF was centrifuged twice to remove cells and biological debris. The supernatant was concentrated and EVs isolated using size-exclusion chromatography. Sample fractions were measured with nanoparticle tracking analysis (NTA) for particle number and size, and transmission electron microscopy and confocal laser scanning microscopy were used to visualize EVs. The described method was able to isolate and preserve EVs. The mean EV size was 247 ± 35 nm (SD) in the EA horses and 261 ± 47 nm in the controls by NTA. The mean concentration of EVs was 1.38 × 1012 ± 1.42 × 1012 particles/mL in the EA horses and 1.33 × 1012 ± 1.07 × 1012 particles/mL in the controls with no statistically significant differences between the groups. With Western blotting and microscopy, these particles were documented to associate with hyaluronan and EV protein markers (CD63, TSG101, HSP70, EMMPRIN, and actin). Equine BALF is rich in EVs of various sizes, and the described protocol is usable for isolating EVs. In the future, the role of EVs can be studied in horses with airway inflammation.